2022
DOI: 10.1177/17562864211062821
|View full text |Cite
|
Sign up to set email alerts
|

Brain biopsy in patients with CLIPPERS syndrome: why and when? A case report and literature review

Abstract: CLIPPERS (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) is an inflammatory disorder of the central nervous system (CNS), predominantly involving the brainstem with a characteristic magnetic resonance imaging (MRI) appearance and clinical and radiological responsiveness to glucocorticosteroids. Yet diagnostic biomarkers are missing and other immune-mediated, (para-) infectious and malignant causes mimic CLIPPERS-like MRI presentations. We report the case of a 51-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The transmural infiltration of lymphocytes, mainly CD3-positive or CD4-positive cells, into the perivascular region is the key pathological hallmark of CLIPPERS [1, 7, 8]. Recent reports suggest that the perivascular infiltration of CD20-positive B lymphocytes is another pathological characteristic of CLIPPERS and is the first sign of its possible transformation into a lymphoma [9, 10]. The detailed mechanism of how white blood cells (mainly T cells) infiltrate the perivascular space of the brainstem is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmural infiltration of lymphocytes, mainly CD3-positive or CD4-positive cells, into the perivascular region is the key pathological hallmark of CLIPPERS [1, 7, 8]. Recent reports suggest that the perivascular infiltration of CD20-positive B lymphocytes is another pathological characteristic of CLIPPERS and is the first sign of its possible transformation into a lymphoma [9, 10]. The detailed mechanism of how white blood cells (mainly T cells) infiltrate the perivascular space of the brainstem is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…a lymphoma [9,10]. The detailed mechanism of how white blood cells (mainly T cells) infiltrate the perivascular space of the brainstem is currently unknown.…”
Section: Case Reports In Neurologymentioning
confidence: 99%
“…3,5 To find previous lymphoma-associated cases up to November 2023, PubMed and Scopus online databases were searched using the keywords "CLIPPER" and "Lymphoma". To the best of our knowledge, 20 patients with lymphoma-associated CLIPPERS have been reported [6][7][8][9][10][11][12][13][14][15][16] since the first introduction of CLIPPERS. 2 A review of 10 patients by Zhang et al showed that patients with lymphoma-associated CLIPPERS had worse clinical outcomes and higher risk of mortality compared to those without lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considering all the studies and cases, there are still no clear guidelines for diagnostics, in order to ensure correct diagnosis in every patient with red flags or atypical presentation. Therefore, these patients should have a stereotactic brain biopsy performer [15,16]. Also, patients in whom lesions did not respond to treatment should have a biopsy conducted [16].…”
Section: Discussionmentioning
confidence: 99%